SNA A NEW DOING IN NURSING CARE ACTIVITY BASED ON EDGAR MORIN'S COMPLEXITY - Fernanda Lucas Lopes; Michelle da Silveira Chapacais Szewczyk; Valéria Lerch Lunardi; Silvana Sidney Costa Santos (Universidade Federal do Paraná, 2007)
Theoretical reflection whose objective was to accomplish an approach of Systematization of NursingAssistance (SNA)with Edgar Morin's Complexity. SNAis a tool used in nursing and in daily caring/care, meaning a new way to exercise and to look atthe caring act. This study made possible to perceive SNA as an indispensable tool for nursing care, pointing out that each individual,that is under nursing care, presents specific and multidimensional characteristics, besides highlighting human being's complexity,enabling its approach with the principles of the complexity proposed by Edgar Morin.